Measuring Copenhagen’s public transport accessibility and network performance in a European context - Scheurer, Jan (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
Spatial accessibility measures have gained prominence in recent years as a supportive tool for decision making as well as stakeholder engagement in integrated land use and transport planning. They have also advanced our ability to conduct comparative and benchmarking studies between the land use-transport systems in different cities, or in a particular city over a longitudinal time line. This paper is based on a public transport accessibility assessment done for metropolitan Copenhagen in 2012 as part of the roll-out of the Spatial Network Analysis for Multimodal Urban Transport Systems (SNAMUTS) tool over a sample of eleven European cities. SNAMUTS utilises a set of seven distinct accessibility indicators to highlight the performance of the public transport network in its urban context from different angles. The application of the tool to Copenhagen showed that the Danish capital is among the top European performers on the majority of these accessibility measures, yet when it comes to actual usage of public transport (expressed by city-wide mode share or number of annual trips per capita), it only occupies a mid-field position in a European context. A more specific comparison of public transport accessibility in Copenhagen with neighbouring Hamburg, using the results of particular SNAMUTS indicators, will serve to highlight some of the key strengths and weaknesses in Copenhagen’s interplay of public transport and urban structure, and inspire some concluding reflections on how the city might use its existing and potential accessibility strengths to attract a higher rate of public transport ridership in the future.